Menyiapkan Generasi Pancasila: Urgensi Pendidikan Multikultural di Era Digital - Sapuadi Sapuadi; Fathor Rosi (Indo Publishing, 2026)
The digital era poses new challenges to the preservation of Indonesia's national diversity, ranging from algorithmic polarization and SARA-based hoaxes to ethical biases in artificial intelligence (AI) targeting the youth. This research aims to analyze multicultural challenges in cyberspace and formulate strategies for instilling Pancasila values through adaptive multicultural education for teenagers as digital natives. The research method employed is qualitative descriptive with a library research approach. The findings indicate that free digital spaces frequently transform into echo chambers that trigger intolerance and erode local cultural identity due to global homogenization. As a transformative solution, integrating multicultural education through the Merdeka Curriculum specifically via the Project for Strengthening the Profile of Pancasila Students (P5) and differentiated learning proves effective in fostering the characters of Global Diversity and Critical Thinking as students' cognitive filters and digital empathy. Furthermore, the success of this movement requires synergy among the Tri Sentra Pendidikan (schools, families, and communities) and the formulation of Pancasila Ethics as a moral direction for future technology development (such as AI). This study concludes that grounding Pancasila in virtual spaces is no longer just a curricular choice, but an urgent long-term strategic investment to safeguard the fabric of Indonesian nationhood on the global stage.